Does financial development matter for innovation in renewable energy?. Issue 21 (15th December 2019) - Pham, Linh
ABSTRACT: This letter investigates a missing link in the literature – whether financial development matters for renewable energy innovation. Our analysis of 22 OECD countries between 1990 and 2014 suggests the crucial role of financial development in the development of both biomass and non-biomass renewable technologies. Additionally, the impact of financial development varies with countries' carbon intensity and innovation growth rate.